2004
DOI: 10.1177/0363546504263946
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Kinematic Influences of a Total Infrapatellar Fat Pad Resection on the Knee

Abstract: The infrapatellar fat pad may have a biomechanical function and may play a role in anterior knee pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…Patella infera after TKA has been reported in 10%65% of cases and has been linked to patellar eversion, radical excision of the fat pad, and lateral release. 5,6 In a prospective randomized controlled trial of 84 patients who had either TKA or UKA, 7 Weale et al reported 34% (14 of 41) of the TKA group developed patella infera, defined as 10% or more shortening of the patellar tendon postoperatively, compared with 5% (two of 43) in the UKA group. None of the above studies have reported an effect of fat pad excision on patellar tendon height five years following total knee replacement (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Patella infera after TKA has been reported in 10%65% of cases and has been linked to patellar eversion, radical excision of the fat pad, and lateral release. 5,6 In a prospective randomized controlled trial of 84 patients who had either TKA or UKA, 7 Weale et al reported 34% (14 of 41) of the TKA group developed patella infera, defined as 10% or more shortening of the patellar tendon postoperatively, compared with 5% (two of 43) in the UKA group. None of the above studies have reported an effect of fat pad excision on patellar tendon height five years following total knee replacement (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 The main function of the Hoffa's fat pad is not fully understood. It is considered to be associated with knee kinetics and patellar biomechanics, 3 express algesic molecules such as the substance P, and cause pain in the anterior knee compartment. 8 In the acute phase of Hoffa's syndrome, inflammation occurs following impingement, fibrin-hemosiderin builds up in macrophages and degenerative lipocytes develop.…”
Section: Discussionmentioning
confidence: 99%
“…However, its endocrine functions are not fully understood. 3 Wicham et al 4 showed that the IFP contains multipotent root cells capable of changing into chondrocyte, osteoblast and adipocyte cells under suitable culture conditions. In recent years, many radiologists and clinicians have been working on the development of IFP into metaplasia and chondroma due to these mesenchymal cells.…”
mentioning
confidence: 99%
“…Second, shortening of the patellar tendon may arise with fat pad resection [2426]. Third, fat pad resection has an influence on the biomechanics of the knee joint [33], as it seems to stabilize the knee joint, especially during extremes of knee motion (flexion angles of less than 20° and greater than 100°) [6]. …”
Section: Discussionmentioning
confidence: 99%